Pemberdayaan Masyarakat dalam Pencegahan Sindrom Metabolik melalui Pemeriksaan Kesehatan dan Edukasi Pola Hidup Sehat - Hamzah Taza; Suparta Mahmuddin; Hasdi Samad (Celebes Health Journal, 2025)
Metabolic syndrome is a growing public health problem in Indonesia and is closely linked to an unbalanced diet and lack of physical activity. This condition directly impacts the high incidence of hyperglycemia, dyslipidemia, and other metabolic disorders at the community level. Therefore, this community service program was implemented to improve nutritional literacy and public awareness of the importance of physical activity through basic health checks and education on healthy lifestyles. The implementation method included participant registration, blood sugar, uric acid, and cholesterol levels were checked, interactive education on a balanced nutritional diet was provided, and changes in participant knowledge and attitudes were measured. The results showed that some participants had relatively high blood sugar and cholesterol levels, particularly among women, while men tended to have higher uric acid levels. The education provided increased participants' understanding of the risks of metabolic syndrome and encouraged changes in attitudes towards diet and daily physical activity. Overall, this activity successfully raised participants' awareness of the importance of metabolic syndrome prevention. These findings confirm that health check-based education is an effective approach to changing behavior and can be developed into a sustainable program at the community level.